2023
DOI: 10.3390/molecules28031190
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Justicia Genus: Insights into Its Chemical Diversity and Biological Potential

Abstract: The genus Justicia has more than 600 species distributed in both hemispheres, in the tropics and temperate regions, and it is used in the treatment of numerous pathologies. This study presents a review of the biological activities of plant extracts and isolated chemical constituents of Justicia (ACANTHACEAE), identified in the period from May 2011 to August 2022. We analyzed over 176 articles with various biological activities and chemical compound descriptions present in the 29 species of Justicia. These have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 148 publications
1
2
0
Order By: Relevance
“…A different study observed similar trend for these haematological parameters with a normal WBC in curative and suppressive tests on the antioxidant and antimalarial activity of the ethanol stem bark extract of Terminalia macroptera in P. berghei-infected mice [44]. The haematinic properties of the extract in this study may be due to the presence of avonoid compounds that have been reported to increase iron absorption and deposition in tissues while reducing iron excretion [45]. In addition, many antimalarial herbal preparations may exert their anti-infective activity not only by affecting the parasite directly but may also stimulate the defensive system of the host through many other mechanisms [46].…”
Section: Discussionsupporting
confidence: 81%
“…A different study observed similar trend for these haematological parameters with a normal WBC in curative and suppressive tests on the antioxidant and antimalarial activity of the ethanol stem bark extract of Terminalia macroptera in P. berghei-infected mice [44]. The haematinic properties of the extract in this study may be due to the presence of avonoid compounds that have been reported to increase iron absorption and deposition in tissues while reducing iron excretion [45]. In addition, many antimalarial herbal preparations may exert their anti-infective activity not only by affecting the parasite directly but may also stimulate the defensive system of the host through many other mechanisms [46].…”
Section: Discussionsupporting
confidence: 81%
“…Te genus Justicia, with over 600 species of scandent perennial herbs and shrubs, represents the largest genus in the family Acanthaceae [1]. Its species are usually found in warm and temperate regions of the world including Africa, Asia, and America.…”
Section: Introductionmentioning
confidence: 99%
“…20 Several biologically active chemical compounds, such as apigenin, naringenin, phytol, etc., were also identified in the plant of the same genus, Justicia gendarussa Burm. 21 J. schimperiana demonstrated antibacterial, 18,22 antidiarrheal, 13 antimalarial, 15,23,24 anti-diabetic, 25 hepatoprotective, 26 anti-asthmatic, [27][28][29] wound healing, 17 antifungal, 14,22,30 and anti-rabies 16,31 activities.…”
Section: Introductionmentioning
confidence: 99%